Limitaciones de la complejidad en las ciencias ómicas: simplificación epistemológica en el abordaje de enfermedades - Delvitto, Ailin (2023)
Omic Sciences are presented as having the potential to carry out complex approaches to the phenomena they study, as well as the capacity to intervene on human health through the development of technologies for diagnosis and treatment of disease. In this regard, we show an epistemological analysis of the use and scope of complex conceptualizations of gene action in the genotype-phenotype relationship in Omic Sciences. In particular, we focus on whether or not epistemological simplifications occur when human diseases are studied Our comparative analysis shows that, in general, in Omic Sciences there are both simple and complex conceptualizations of gene action in the genotype-phenotype relationship, while in omics investigations that address human diseases an exacerbation of simplifying conceptualizations is found. It is discussed whether this epistemological simplification is favored in scenarios of intervention in human health, such as the generation of knowledge for the development of Omics technologies for improved diagnosis and treatment of disease. Overall, as in other fields of Natural Sciences, in omics studies of disease a necessary link between epistemological simplifications and the promise of intervention is found.